Production, consumption, business and the economy structural ideals and moral realities - Wood, Donald C. (Emerald, 2014)
This thirty-fourth volume in the REA series contains fourteen chapters by a variety of researchers touching on a wide range of topics in economic anthropology and covering a vast geographical area. The chapters are divided into four sections: one focusing on commodities and their social meanings and values, one organized around the anthropological investigation of business systems and practices, one concentrating on the economic importance of productive land in culture and society, and finally one that showcases a variety of new research on the economic anthropology of Latin America. Geographic areas featured in the volume include Africa (Kenya and Mauritius), Europe (Britain, Germany, and Romania), North America (Mexico and Guatemala), South America (Brazil), East Asia (Japan), and Western Asia (Jordan). Standing apart from these four sections is a special feature essay by noted anthropologist Sidney Greenfield that calls for a re-evaluation of the global capitalist system as it stands today.
Keywords: Economic anthropology.; Economics -- Moral and ethical aspects.; elektronické knihy; electronic books